Peran Investasi Asing Langsung dan Bantuan Luar Negeri dalam Mendorong Pertumbuhan Ekonomi: Efek Moderasi Stabilitas Politik Di Negara D-8 - Mubarak AS, Muh Afdhal; Ibnu Muhdir (Jurnal Magister Ekonomi Syariah, 2023)
The economic growth of D-8 countries is influenced by factors such as foreign aid, foreign direct investment (FDI), and political stability. This study analyzes the impact of these variables on the economic growth of developing countries in the Organization for Islamic Cooperation (OIC). Data collected from 2012 to 2021 were analyzed using Eviews 9 software. The results of the analysis indicate that foreign aid has a significant and positive effect on economic growth. Foreign aid promotes domestic investment, accelerates economic growth, and reduces development gaps. Additionally, foreign direct investment also contributes positively to the economic growth of developing countries through technology transfer, access to new markets, job creation, and increased domestic investment. Creating an environment that supports FDI is crucial, including clear investment policies, legal protection, and adequate political stability. Political stability plays an important role in strengthening the influence of foreign aid on economic growth. For future research, it is recommended to deepen the understanding of the interaction between foreign aid, foreign direct investment, and political stability in the context of economic growth in developing countries. Other factors that can affect economic growth should also be considered. The findings of this study provide valuable insights for policymakers in creating favorable conditions for economic growth and development in developing countries.